2015
DOI: 10.1093/jb/mvv066
|View full text |Cite
|
Sign up to set email alerts
|

In vitrodihydrouridine formation by tRNA dihydrouridine synthase fromThermus thermophilus, an extreme-thermophilic eubacterium

Abstract: Dihydrouridine (D) is formed by tRNA dihydrouridine synthases (Dus). In mesophiles, multiple Dus enzymes bring about D modifications at several positions in tRNA. The extreme-thermophilic eubacterium Thermus thermophilus, in contrast, has only one dus gene in its genome and only two D modifications (D20 and D20a) in tRNA have been identified. Until now, an in vitro assay system for eubacterial Dus has not been reported. In this study, therefore, we constructed an in vitro assay system using purified Dus. Recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…While the stability and (non-)isostericity of individual base pairs (e.g., GC versus GU) can increase the local flexibility in a tRNA domain [137], there are also modifications that contribute to the conformational elasticity of these molecules. Dihydrouridine (D, see Figure 3C for a three dimensional structure) is the name-giving modification that is frequently found in the D-loop, predominantly at positions 16, 17, 20, 20a and 20b, and additionally at position 47 in the variable loop [18,27,99,138,139,140,141,142,143]. It is formed by a reduction of the double bond between positions C5 and C6 in the pyrimidine ring of uridine [144].…”
Section: Structural Impact Of Modificationsmentioning
confidence: 99%
“…While the stability and (non-)isostericity of individual base pairs (e.g., GC versus GU) can increase the local flexibility in a tRNA domain [137], there are also modifications that contribute to the conformational elasticity of these molecules. Dihydrouridine (D, see Figure 3C for a three dimensional structure) is the name-giving modification that is frequently found in the D-loop, predominantly at positions 16, 17, 20, 20a and 20b, and additionally at position 47 in the variable loop [18,27,99,138,139,140,141,142,143]. It is formed by a reduction of the double bond between positions C5 and C6 in the pyrimidine ring of uridine [144].…”
Section: Structural Impact Of Modificationsmentioning
confidence: 99%
“…To clarify the effect by D20 modification on tRNA modification network, we recently analyzed the dihydrouridine synthase gene disruptant strain of T. thermophilus (Kusuba et al . ). Unexpectedly, the absence of D20 did not cause any effect on the tRNA modification network at 50 and 70 °C.…”
Section: Discussionmentioning
confidence: 97%
“…; Kusuba et al . ; Takuma et al . ), we reported that modified nucleotides in tRNA and tRNA modification enzymes in T. thermophilus form a network and that this network changes the degrees of modifications in tRNAs according to the temperature of the culture.…”
Section: Introductionmentioning
confidence: 99%
“…The substrate specificities of Dus enzymes were determined for model organisms such as E. coli, Saccharomyces cerevisiae and T. thermophilus Dus (26,(28)(29)(30). In the case of the yeast enzymes, the specificities of the four Dus are well known.…”
Section: The Dihydrouridine Synthases: a Large Family Of Flavoenzymesmentioning
confidence: 99%
“…As a matter of fact, the function of Dus B is unknown and the enzymes that synthesize D 17 , D 20a in tRNA and D 2449 in rRNA remain to be established ( Figure 1B). Recently, Hori's group showed that in T. thermophilus, D20 and D20a are derived from the activity of one single Dus (Dus TT ) belonging to DusA subfamily (29). Another interesting feature that remains to be elucidated concerns Mycoplasma mycoides whose genome encodes for a single Dus while its tRNAs contain D at many different positions (30).…”
Section: The Dihydrouridine Synthases: a Large Family Of Flavoenzymesmentioning
confidence: 99%